THE INFLUENCE OF AUDIO-VISUAL LEARNING MEDIA ON EARLY CHILDHOOD LANGUAGE DEVELOPMENT - Asraty Poku (Indonesian Journal of Education (INJOE), 2025)
This research aims to examine the influence of audio-visual learning media on early childhood language development through a literature review approach. Language development in early childhood is an important aspect that forms the basis for children's subsequent communication, thinking and learning abilities. Audio-visual media, which combines elements of sound and images, is believed to be able to provide effective stimulation in improving children's language skills, both from the receptive (hearing and understanding) and expressive (speaking and expressing ideas) aspects. This study analyzes various scientific sources such as journals, books and articles in the last ten years, using a content analysis and thematic synthesis approach. The study results show that audio-visual media can enrich children's language environment, expand vocabulary, and help understand language structures contextually, especially if their use is accompanied by interaction with teachers or parents. However, the effectiveness of this media is very dependent on the quality of the content, duration of use, and the active involvement of the companion in the learning process. Thus, audio-visual media has great potential to become an effective learning aid if applied appropriately and wisely in early childhood education.